THE IMPACT OF ARTIFICIAL INTELLIGENCE ON AUDIT QUALITY: THE MODERATING ROLE OF AUDITOR COMPETENCE - Vince Ariany (Penelitian dan Pengembangan Ilmu, 2026)
This study critically reviews the extant literature on the relationship between artificial intelligence (AI) adoption and audit quality, with particular attention to the moderating role of auditor competence. A narrative review approach is adopted, synthesizing peer-reviewed studies, professional-body reports, and regulatory publications, primarily published between 2018 and 2026 and drawn from Scopus-indexed and other reputable outlets. The review is anchored on Agency Theory and the Technology Acceptance Model (TAM) to construct an integrative conceptual framework. The reviewed literature indicates that AI can enhance audit quality through expanded data coverage, faster anomaly detection, and more consistent risk assessment, yet these benefits are neither automatic nor uniform. A recurring